The Big Cheese [book with audioplayer] - John, Jory; Oswald, Pete (John, Jory. Food group., 2023)
"Don't miss the seventh picture book in the #1 New York Times bestselling Food Group series from Jory John and Pete Oswald! The Big Cheese is the best at everything, and brags about it, too. When the annual Cheese-cathlon comes around, the Big Cheese is prepared to win, as always. But what happens when the quiet new kid, Wedge Wedgeman, comes out on top? Is a slice of humility all the Big Cheese needs to discover that some things are better than being the best?"--VOX publishing website.